Differencing the Canon : Feminist Desire and the Writing of Art's Histories - Pollock, Griselda (London, New York : Routledge, 1999)
About canons and culture wars -- Differencing: feminism's encounter with the canon -- The ambivalence of the maternal body: re/drawing Van Gogh -- Fathers of modern art: mothers of invention: cocking a leg at Toulouse-Lautrec -- The female hero and the making of a feminist canon: Artemisia Gentileschi's representations of Susanna and Judith -- Feminist mythologies and missing mothers: Virginia Woolf, Charlotte Bronte, Artemisia Gentileschi and Cleopatra -- Revenge: Lubaina Himid and the making of new narratives for new histories -- Some letters on feminism, politics and modern art: when Edgar Degas shared a space with Mary Cassatt at the suffrage benefit exhibition, New York 1915 -- A tale of three women: seeing in the dark, seeing double, at least, with Manet
boek